2016
DOI: 10.1590/1982-0194201600037
|View full text |Cite
|
Sign up to set email alerts
|

Fatores relacionados à flebite em idosos com infusão intravenosa de amiodarona

Abstract: Objective: To verify the incidence of phlebitis and identify factors associated with the development of phlebitis due to peripheral intravenous infusion of amiodarone in elderly patients. Methods: Prospective and observational cohort study on risk factors for the development of phlebitis in patients aged over 60 years, who received peripheral intravenous infusion of amiodarone, hospitalized in 2012 in the coronary care (22 beds) and general semi-intensive units (43 beds) of a large private hospital in São Paul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
(32 reference statements)
0
10
0
7
Order By: Relevance
“…Vein quality control through palpation and visual inspection can prevent phlebitis as well as the nurse's duration of hand hygiene and the clinical experience [55]. Regarding the choice of veins, a controversy has been found, as some studies recommend the forearm as it has a larger diameter and this reduces rates of phlebitis in the region, but there are many others that claim that this region should be avoided, in addition to the joints and wrist areas (category IA), for having a higher incidence of mechanical phlebitis related to catheter movement [4,56]. A review of the literature concluded that veins from the antecubital region are associated with lower rates of phlebitis, as compared to veins in the hands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vein quality control through palpation and visual inspection can prevent phlebitis as well as the nurse's duration of hand hygiene and the clinical experience [55]. Regarding the choice of veins, a controversy has been found, as some studies recommend the forearm as it has a larger diameter and this reduces rates of phlebitis in the region, but there are many others that claim that this region should be avoided, in addition to the joints and wrist areas (category IA), for having a higher incidence of mechanical phlebitis related to catheter movement [4,56]. A review of the literature concluded that veins from the antecubital region are associated with lower rates of phlebitis, as compared to veins in the hands.…”
Section: Discussionmentioning
confidence: 99%
“…There are higher rates of phlebitis when larger caliber catheters are used, as they increase attraction to the vessel wall, so the smallest possible length and caliber catheters (Category IB) are recommended [4,56].…”
Section: Discussionmentioning
confidence: 99%
“…14 A faixa etária mais acometida é de pacientes com idade superior a 60 anos, pois os idosos possuem grau elevado de fragilidade capilar e a túnica íntima do vaso com maior tendência a desenvolver processos inflamatórios. 6,18 Isso evidencia a necessidade de maior atenção da equipe de assistência com os idosos em uso de AVPs, já que a idade é considerada fator predisponente para a ocorrência de flebite.…”
Section: Discussionunclassified
“…Ademais, os idosos muitas vezes apresentam grande número de comorbidades, acarretando em agravamento do estado de saúde e maior número de drogas utilizadas, repercutindo em piora da fragilidade na rede vascular 19 . O tipo e a forma de fixação do cateter periférico também estão relacionados, o que acarreta aumento no número de punções, potencializando os danos na rede venosa periférica, maior risco de infecção, dor e desconforto 20 .…”
Section: Discussionunclassified